(Dys)Prosody in Parkinson’s disease: effects of medication and disease progression on intonation and prosodic phrasing - Frota, Sónia (2022)
Abstract: The phonology of prosody has received little attention in studies of motor speech disorders. The present study investigates the phonology of intonation (nuclear contours) and speech chunking (prosodic phrasing) in Parkinson’s Disease (PD), as a function of medication intake and progression of the disease. Following methods of the prosodic and intonational phonology frameworks, we examined the ability of 30 PD patients to use intonation categories and prosodic phrasing structures in ways similar to 20 healthy controls to convey similar meanings. Speech data from PD patients were collected before and after a dopaminomimetic drug intake and were phonologically analyzed in relation to nuclear contours and intonational phrasing. Besides medication, disease duration and presence of motor fluctuations were also factors included in the analyses. PD patients showed a decreased ability to use nuclear contours and prosodic phrasing. Medication improved intonation regardless of disease progression, but did not help with dysprosodic phrasing. In turn, disease duration and motor fluctuations affected phrasing patterns, but had no impact on intonation. Our study demonstrated that the phonology of prosody is impaired in PD, and prosodic categories and structures may be differently affected, with implications for the understanding of PD neurophysiology and therapy.